PENGARUH ANALISIS TINGKAT KESUKARAN BUTIR SOAL PENILAIAN TENGAH SEMESTER DAN AKHIR SEMESTER PELAJARAN PKN KELAS V SDN 1 BAADIA - Gawise, Gawise (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of difficulty of the mid-semester and final semester assessment questions for Civics for grade V of SD Negeri 1 Baadia. The sample of this study was all 32 grade V students. The data collection technique was documentation. The data was analyzed using the AnatesV application. The results of the study showed that the analysis of the questions from the mid-semester and final semester assessment exams in Civics for grade V of SD Negeri 1 Baadia in the 2024/2025 academic year, seen from the aspect of difficulty level, the researcher found that out of 20 questions, there were 14 easy questions (70%) and 6 medium questions (30%). In the final semester assessment of Civics for grade V, it was found that in the multiple-choice questions out of 20 questions, there were 14 easy questions (70%) and 6 medium questions (30%). Meanwhile, in the fill-in and description, there are 20 questions (10 fill-in questions and 10 essay questions), there are 13 questions in the medium category (60%) and 7 questions in the easy category. From these results, the level of difficulty of the questions is still not good and needs improvement because the questions created are not balanced and do not even have a difficult category.